2018
DOI: 10.1021/jacs.8b06079
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Properties of Core-Expanded Azacoronene Analogue: A Twisted π-System with Two N-Doped Heptagons

Abstract: A core-expanded, pyrrole-fused azacoronene analogue containing two unusual N-doped heptagons was obtained from commercially available octafluoronaphthalene and 3,4-diethylpyrrole in two steps as a heteroatom-doped nonplanar nanographene. Full fusion with the formation of the tetraazadipleiadiene framework and the longitudinally twisted structure was unambiguously confirmed by single-crystal X-ray diffraction analysis. The edge-to-edge dihedral angle along the acene moiety was 63°. This electron-rich π-system s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 33 publications
(11 reference statements)
3
63
0
1
Order By: Relevance
“…The same research group also reported the DDQ‐mediated synthesis of compounds 180 and 181 , expanded derivatives of 177 containing one or two methylene bridges in the outer hexapyrrole rim . Another spectacular case of multiple intramolecular oxidative aromatic coupling involving eight pyrrole units to form a twisted aza‐PAH containing two unusual N‐doped heptagons was revealed by Uno and co‐workers …”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 89%
See 1 more Smart Citation
“…The same research group also reported the DDQ‐mediated synthesis of compounds 180 and 181 , expanded derivatives of 177 containing one or two methylene bridges in the outer hexapyrrole rim . Another spectacular case of multiple intramolecular oxidative aromatic coupling involving eight pyrrole units to form a twisted aza‐PAH containing two unusual N‐doped heptagons was revealed by Uno and co‐workers …”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 89%
“…[186] Another spectacular case of multiple intramolecular oxidative aromatic coupling involving eight pyrrole units to form at wisted aza-PAH containing two unusual N-doped heptagons was revealed by Uno and coworkers. [187] Osuka and co-workers reported yet another example of an efficient intramolecular oxidative coupling of pyrrole rings (Figure 14). Tetrapyrrole [8]circulene analogue 182 was prepared by employing aso-called "fold-in" strategy, [188] which is am ethod developed earlier by Stępień and co-workers to construct strained macrocycles by contraction of the larger, less-strained precursors.…”
Section: Dyes and Heterocyclic Polyarenesmentioning
confidence: 99%
“…With the growing number of unprecedented curved aza‐nanographenes published within the last five years, this study offers both general understanding of their optical behavior and guidelines for designing solvatofluorochromic dyes possessing large fluorescence quantum yield across the solvent polarity scale.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Inclusion of heteroatoms or nonbenzenoid rings in such systems can have ap rofound effect on their electronic and chiroptical characteristics.H owever,s uch modifications are synthetically challenging and thus rarely attempted. Hexapyrrolohexaazacoronene [HPHAC(1); Figure 1] [28,29] and its analogues [30][31][32][33][34] are attractive heteroaromatic cores for helical expansion because of their tunable optical and electrochemical signatures and the variety of functionalization methods now available. Additionally,H PHACs ystems are obtained by oxidative annulation of hexapyrrolylbenzene (HPB), which is inher-ently ap ropeller-shaped molecule,a nd adopts ac hiral (though non-rigid) conformation with D 6 symmetry.…”
mentioning
confidence: 99%